The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1002/ajmg.b.32604
|View full text |Cite
|
Sign up to set email alerts
|

Ancestry‐specific and sex‐specific risk alleles identified in a genome‐wide gene‐by‐alcohol dependence interaction study of risky sexual behaviors

Abstract: We previously mapped loci for the genome-wide association studies (GWAS) and genome-wide gene-by-alcohol dependence interaction (GW-GxAD) analyses of risky sexual behaviors (RSB). This study extends those findings by analyzing the ancestry- and sex-specific AD-stratified effects on RSB. We examined the concordance of findings for the AD-stratified GWAS and the GW-GxAD analysis of RSB, with concordance defined as genome-wide significance in one analysis and at least nominal significance in the second analysis. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 53 publications
0
20
0
Order By: Relevance
“…Inhibition of FAM134A causes impaired proteostasis in the endoplasmic reticulum due to the accumulation of misfolded proteins, which has been implicated in vascular dementia [ 45 ]. FAM162A is associated by GWAS to a gene-by-alcohol dependence interaction study of risky sexual behaviors and so it could be related to behavioral control [ 46 ]. Coincidentally, ADHD is associated with increased sexual risk taking [ 47 ].…”
Section: Resultsmentioning
confidence: 99%
“…Inhibition of FAM134A causes impaired proteostasis in the endoplasmic reticulum due to the accumulation of misfolded proteins, which has been implicated in vascular dementia [ 45 ]. FAM162A is associated by GWAS to a gene-by-alcohol dependence interaction study of risky sexual behaviors and so it could be related to behavioral control [ 46 ]. Coincidentally, ADHD is associated with increased sexual risk taking [ 47 ].…”
Section: Resultsmentioning
confidence: 99%
“…Here we unexpectedly observed a profound decrease of Avpi1 transcript levels in the nPE1 +/+ hypothalamus after chronic alcohol drinking (Figure D), suggesting for the first time the potential interaction between the AVP‐induced protein 1 and excessive alcohol drinking or withdrawal. Of interest, in a recent human genetic study, rs7913179 variant in the Avpi1 gene is found to associate with alcohol dependency in a genome‐wide gene‐by‐alcohol dependence interaction analysis in European men . Although the AVP/V1b receptor system plays important roles in alcohol drinking, it seems unknown, however, whether and how the hypothalamic AVP‐induced protein 1 is involved in alcohol drinking behaviors, and further study is needed.…”
Section: Discussionmentioning
confidence: 99%
“…Of interest, in a recent human genetic study, rs7913179 variant in the Avpi1 gene is found to associate with alcohol dependency in a genome-wide gene-by-alcohol dependence interaction analysis in European men. 53 Although the AVP/V1b receptor system plays important roles in alcohol drinking, 11,15 it seems unknown, however, whether and how the hypothalamic AVP-induced protein 1 is involved in alcohol drinking behaviors, and further study is needed.…”
Section: Genetically Determined Differences In Stress Genes Transcrmentioning
confidence: 99%
“…Inhibition of FAM134A causes impaired proteostasis in the endoplasmic reticulum due to the accumulation of misfolded proteins, which has been implicated in vascular dementia [45]. FAM162A is associated by GWAS to a gene-by-alcohol dependence interaction study of risky sexual behaviors and so it could be related to behavioral control [46]. Coincidentally, ADHD is associated with increased sexual risk taking [47].…”
Section: Analysis Of Differentially Expressed Genesmentioning
confidence: 99%